ANORMAL BAŞ POZİSYONLARININ OKÜLER NEDENLERİ - DİKİCİ, Kemal and KIZILKAYA, Melda (Cerrahpaşa Medical Journal, 2014)
Background.- Our study was conducted to evaluate the patients who have abnormal head posture and to determine the frequency of ocular reasons for this abnormality. Design.- One hundred and three male and 84 female patients that were diagnosed to have abnormal head posture and followed in our strabismus department were retrospectively analyzed. Patients. visual acuity levels, duction and version examinations, distance and near deviation angles, Bielschowsky head tilt test, prism cover tests, Worth four dot test, synoptophore examination and Titmus test results were evaluated. Results.- It is determined that different types of strabismus was the reason of abnormal head postures in 80 % of the cases covered in the study which was conducted to evaluate probable compensatory mechanisms of abnormal head postures derived from ophthalmologic reasons. And also in 80 % of all cases incomitance was determined. Conclusion.- Most of the pathologies which cause abnormal head postures have an ocular origin.